Penentuan Status Mutu Air Berdasarkan Indeks Pencemaran Pada Daerah Irigasi Rawa Teluk Bayur - Zuandi, Weli; Normagiat, Sigit (Department of Environmental engineering, Faculty of Science and Technology, Islamic State University Sunan Ampel Surabaya, 2024)
Bayur Bay Swamp Irrigation Area (DIR) has a land area of ​​(70.88 km2), so an irrigation system with sufficient water discharge and appropriate quality of irrigation water is needed.The purpose of this study was to determine the quality and status of DIR Teluk Bayur irrigation water. Based on the regulations in force, the use of water in the DIR is sufficient for class IV quality status, but the problem that occurs in the Teluk Bayur DIR is that the water in the DIR network is used by the community to meet the needs of their daily activities. Where the use of water for daily needs is included in class II water quality. Therefore, it is necessary to measure water quality using the Water Pollution Index (IPA) method to determine the status of water pollution levels in class II water quality based on RI Government Regulation No. 22 Year 2021. From the test results, it was found that the Total Phosphate Parameter was below the quality standard so that based on the calculation results using the Water Pollution Index method, samples SA3 and SA4 were heavily polluted with pollution index values ​​of 12.43 and 12.80, where the maximum Ci/Lij values ​​were respectively respectively are 17.50 and 18.04 while the status of SA1 pollution index value is 1.89 lightly polluted and SA2 pollution index is 4.40 moderately polluted. So that from all water quality tests it can be said that the quality of irrigation water in Teluk Bayur DIR still does not meet all of the quality standard parameters that have been set. 89 are lightly polluted and the SA2 pollution index is 4.40 moderately polluted. So that from all water quality tests it can be said that the quality of irrigation water in Teluk Bayur DIR still does not meet all of the quality standard parameters that have been set. 89 are lightly polluted and the SA2 pollution index is 4.40 moderately polluted. So that from all water quality tests it can be said that the quality of irrigation water in Teluk Bayur DIR still does not meet all of the quality standard parameters that have been set.